Nutrient Optimisation of Crude Glycerin Alternative Feed Formulation for Pearl Catfish (Clarias gariepinus) - Anggraini, Rr. Citra Permata Kusuma; Winarno, Raden Hesti; Firdaus, Syafrizal Akbar; Panjaitan, Dennys (Agrikan Jurnal Agribisnis Perikanan, 2024)
abstrak Crude glycerin is a main byproduct of biodiesel plants that has the potential to be used as a feed ingredient, but has not been fully utilized With the increasing biodiesel production, the quantity of crude glycerin is also rising, which could have environmental impacts if not wisely managed. However, research on using crude glycerin as fish feed in Indonesia is still limited Previous studies have not yet shown optimal results, so further research is needed to optimize the nutrition in feed formulations This study aims to determine the appropriate feed formulation to enhance the nutrition of alternative crude glycerin feed for pearl catfish (Clarias gariepinus). The research method utilized the Pearson square method to formulate feed and conducted proximate analysis to determine the nutritional content of the feed The results of this study indicate that sample code A has a higher protein content of 14,85% compared to sample code B, which is 11,86% Further research is recommended to achieve better results It is suggested to use an oven for drying to ensure complete dryness of the pellets and reduce water content.